ANALISIS KOMPARATIF KINERJA BANK SYARIAH DENGAN PENDEKATAN INDEKS KINERJA ISLAMIC - Lubis, Rini Hayati (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This study aims to determine whether there is a difference between the performance of BNI Syariah Bank and BRI Syariah with the Islamicity Performance Index approach method is one alternative to measure the performance of Islamic banking in terms of IslamicThis method uses quantitative and comparative, as well as data obtained sourced from BNI Syariah and BRI Syariah financial reports in 2014-2018 through the website www.ojk.go.id .The variables used in this study are the ratio of PSR, ZPR, EDR qardh and donations, IIR and IsIR The results of the research test showed that there were significant differences in the PSR ratio while for the ZPR, EDR qardh and donation ratios, IIR and IsIRThere were no significant differences. Overall BNI Syariah's performance is better when compared to BRI Syariah.Based on these results it is expected that Bank Syariah Syariah will further improve financial performance based on Islamic Sharia through strengthening capital, and encourage the development of social funds, namely zakat, infaq, alms and endowments.